2022
DOI: 10.3168/jds.2021-21753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tuberculin skin testing on serological results against Mycobacterium avium ssp. paratuberculosis (MAP): Evidence of distinct effects in MAP-infected and noninfected cows

Abstract: Johne's disease and bovine tuberculosis are diseases of economic, public health, and animal welfare importance. The single intradermal cervical comparative tuberculin (SICCT) test, which is used to determine bovine tuberculosis status as part of eradication schemes in the United Kingdom and some other countries, has been reported to interfere with the results of the widely used ELISA to detect antibodies against Mycobacterium avium ssp. paratuberculosis (MAP) in milk. Better understanding of the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Hence, changes in the number of reactors may occur in other species or epidemiological settings. In this sense, previous studies have reported a booster effect in antibody responses measured via milk and serum ELISAs in PTB-infected cattle herds [ 33 , 34 ]. Kennedy et al [ 33 ] reported a significant increase in the number of cattle reacting to an ELISA test on days 14 and 9 post-PPD inoculation in serum and milk samples, respectively, indicating a faster increase in the responses in milk versus serum samples, similar to what was observed here.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, changes in the number of reactors may occur in other species or epidemiological settings. In this sense, previous studies have reported a booster effect in antibody responses measured via milk and serum ELISAs in PTB-infected cattle herds [ 33 , 34 ]. Kennedy et al [ 33 ] reported a significant increase in the number of cattle reacting to an ELISA test on days 14 and 9 post-PPD inoculation in serum and milk samples, respectively, indicating a faster increase in the responses in milk versus serum samples, similar to what was observed here.…”
Section: Discussionmentioning
confidence: 91%
“…The difficulty in finding goat herds in Spain that are either not infected with PTB or not vaccinated against the disease hinders the possibility to conduct detailed analyses on the impact of specificity. In this sense, the interference caused by a recent CITT in the humoral diagnosis of PTB has been established in cattle, leading to false-positive reactions using serum [ 19 ] and milk samples from PTB-free herds [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The booster effect has also been assessed for the humoral diagnosis of paratuberculosis (PTB), another mycobacterial disease affecting domestic ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP) ( 29 , 30 ). In this regard, a recent CITT may maximize the Se of PTB humoral techniques in PTB-infected herd ( 30 ), although an impact on the Sp observed PTB-free herds has been also described ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (MAP) ( 29 , 30 ). In this regard, a recent CITT may maximize the Se of PTB humoral techniques in PTB-infected herd ( 30 ), although an impact on the Sp observed PTB-free herds has been also described ( 29 ).…”
Section: Discussionmentioning
confidence: 99%